2012
DOI: 10.1016/j.micinf.2012.06.004
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of colonization with Staphylococcus aureus clone USA300 at multiple body sites among sexually transmitted disease clinic patients: an unrecognized reservoir

Abstract: Extranasal colonization is increasingly recognized as an important reservoir for Staphylococcus aureus among high-risk populations. We conducted a cross-sectional study of multiple body site colonization among 173 randomly selected STD clinic patients in Baltimore, Maryland. Staphylococcal carriage at extranasal sites, including the oropharynx, groin, rectum, and genitals, was common among study subjects. The USA300 clone was particularly associated with multiple sites of colonization compared with non-USA300 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 11 publications
(15 reference statements)
1
22
0
Order By: Relevance
“…The majority of our study population was Hispanic, which has previously been associated with lower MRSA colonization in PLWH [27]. Although we did not observe significant gender differences between S aureus carriage in the current study, we recently observed that men attending a sexually transmitted disease clinic were almost 4 times more likely to harbor S aureus in the anterior nares [15]. Gym use was significantly associated with S aureus colonization ( P = .019), but it was not associated with MRSA colonization ( P = .067), which might be explained by our relatively small sample size.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The majority of our study population was Hispanic, which has previously been associated with lower MRSA colonization in PLWH [27]. Although we did not observe significant gender differences between S aureus carriage in the current study, we recently observed that men attending a sexually transmitted disease clinic were almost 4 times more likely to harbor S aureus in the anterior nares [15]. Gym use was significantly associated with S aureus colonization ( P = .019), but it was not associated with MRSA colonization ( P = .067), which might be explained by our relatively small sample size.…”
Section: Discussionmentioning
confidence: 46%
“…The role of S aureus and MRSA colonization in subsequent infections is less clear in the community setting [13]. More recently, colonization of body sites other than the nares have been recognized as potential reservoirs for infecting S aureus strains [14, 15], including in PLWH [6]. These studies have also suggested that certain clonal types such as USA300 and USA500 preferentially colonize certain body sites such as the groin, in particular in patients infected with HIV [16, 17].…”
mentioning
confidence: 99%
“…Close personal contact with household members who have a skin infection may also increase the risk of transmission and young children appear to be particularly important as reservoirs and potential vectors for CA-MRSA [30, 31]. Several studies have also commented on the increase in nasal and extra-nasal colonization with CA-MRSA strains [32] and the potential of household surfaces as sources for transmission or of recurrent infections [28, 30, 33]. However, in many cases, including outbreak (epidemic) and non-outbreak (endemic) CA-MRSA, it is often impossible to identify an endogenous source of the infection, such as nasal colonization, despite the increased risk for subsequent infection in nasal carriers.…”
Section: Case Studiesmentioning
confidence: 99%
“…Community-acquired Methicillin-Resistant Staphylococcus aureus (CA-MRSA) emerged in the community in the 1990s, and is now the leading cause of skin and soft tissue infections (SSTIs) in out-patient settings in the United States of America [2]. Nonetheless, methicillin-susceptible S. aureus (MSSA) still remains an important cause of S. aureus infections [3,4]. …”
Section: Introductionmentioning
confidence: 99%